THE ROLE AND DEVELOPMENT TRENDS OF TACTICS IN THE GLOBAL GEOPOLITICAL ENVIRONMENT (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the role of tactics in the system of military art, its tasks and development trends in modern conditions. The interrelationship between strategy, operational art and tactics is highlighted, and the features of modern joint combat are considered. Also, the impact of technological progress, the expansion of the information field, unmanned systems and high-precision weapons on tactics is scientifically substantiated. The article reveals the modern interpretation of defense and attack and the importance of the combat support system in the tactical process.
Keywords: Tactics, military art, strategy, operational art, joint combat, attack, defense, combat support, maneuver, military technologies.